Iatrogenic infection by atypical mycobacteria: a case report of M. phlei infection in an immunocompetent patient simulating breast malignancy - Carlos Salomon Sáenz de-León; Rogelio de Jesus Treviño-Rangel; Ricardo Olvera Calderón; Diego Carrion-Álvarez; Carlos Alberto Calderón Díaz; Hiram Villanueva-Lozano (Journal of Infection in Developing Countries, 2025)
Introduction: Atypical nontuberculous mycobacteria (NTM) constitute a diverse group of environmental organisms capable of causing infections in immunocompromised patients. Mycobacterium phlei has limited documentation of clinical disease in the literature.